The impact on student achievement of an assessment for learning teacher professional development program. (September 2022) - de Vries, J.A.; Dimosthenous, A.; Schildkamp, K.; Visscher, A.J.
Abstract: Assessment for Learning (AfL) can increase student achievement. However, teachers find implementing AfL coherently difficult, as it requires complex professional competence. In this experimental study, we investigated the effect on student achievement of teacher professional development for AfL based on the dynamic approach ( n teachers = 41, n students = 599) . The dynamic approach includes four principles: (1) a competence-based approach, (2) adapting to teachers' needs, (3) explaining underlying mechanisms, and (4) supporting teachers in acquiring the competences. We found a positive effect ( d = 0.27) on student achievement. Recommendations for teacher professional development and future research are presented. Highlights: The dynamic approach to teacher professional development has a positive impact on student achievement. A differentiated, whole-task program is a suitable approach for teacher professional development for complex competences. Differentiation for teachers should be based on more comprehensive data about their professional needs.